High-toughness and high-conductivity epoxy resin composition as well as preparation method and application thereof
By introducing fillers such as carbon nanotubes, graphene and spherical conductive carbon black into conductive epoxy resin, a double-conductive network structure is formed, which solves the problems of poor conductivity and low preparation efficiency, and achieves high efficiency and low cost high conductivity Preparation of epoxy resin composition.
Patent Information
- Application Number
- CN202411067247.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-27
AI Technical Summary
The existing conductive epoxy resin has poor electrical conductivity, long process preparation time, complexity and low manufacturing efficiency, resulting in high manufacturing costs.
High toughness and high conductivity epoxy resin composition consisting of matrix resin, core-shell resin, rubber, curing agent, wetting agent, promoter, carbon nanotube, graphene and spherical conductive carbon black, through specific formula ratios and process flow to form a dual conductive network structure to improve conductive performance and manufacturing efficiency.
The conductive properties are significantly improved, process simplified, time shortened, and manufacturing costs are reduced. The composition has excellent conductive properties and an efficient manufacturing process.
Smart Images

Figure BDA0004979705140000081 
Figure BDA0004979705140000091 
Figure BDA0004979705140000092
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical products, and specifically relates to a high-toughness and high-conductivity epoxy resin composition, a preparation method and application thereof. Background Art
[0002] Epoxy resin has excellent bonding strength and can achieve good bonding with most substrates; it has good heat resistance, low curing shrinkage, stable properties, and good chemical resistance. Conductive epoxy resin is composed of epoxy resin filled with randomly distributed metal or conductive carbon particles. The higher the proportion of filling particles, the better the conductivity, but the bonding strength will decrease. Conductive epoxy resin is widely used in the fields of electronics, electrical appliances, automobiles, aviation, medical instruments, etc.; with the continuous development of science and technology, the application prospects of conductive epoxy resin will become more extensive. In the field of electrical appliances, such as inductors, transformers, capacitors, motors, etc., the materials need to have certain toughness and high conductivity. However, most of the conductive epoxy resins on the market have poor conductivity and poor toughness. For example: the invention with the publication number "CN 110256815B" and the name "A method for preparing a toughened conductive epoxy resin composite material" is to grind epoxy resin with graphene, carbon nanotubes, and conductive carbon black by zirconium balls, and then defoam and cure to obtain a toughened conductive epoxy resin composite material. Although it has the characteristics of impact resistance and bending resistance, it has the problem of low conductivity. The invention with the publication number "CN108165198B" and the name "A highly conductive epoxy resin adhesive and its preparation method" obtains a highly conductive epoxy resin adhesive through the conductive synergistic effect of organic metal polymers and carbon-based conductive fillers; but because its conductive filler filling ratio is not high and its mechanical properties are average. There are the following problems: (1) Poor conductivity. (2) The process preparation time is long, the process is complicated, the manufacturing efficiency is low, and the manufacturing cost is high.
[0003] Therefore, it is necessary to develop a conductive epoxy resin with better conductivity, better toughness and higher bonding strength than ordinary conductive epoxy resins. Summary of the invention
[0004] One of the purposes of the present invention is to solve the problems of poor conductivity, long process preparation time, complex process, low manufacturing efficiency and high manufacturing cost of existing conductive epoxy resins, and to provide a high-toughness and high-conductive epoxy resin composition, which has the beneficial effects of excellent conductive performance, short process preparation time, simple process, high manufacturing efficiency and low manufacturing cost.
[0005] The second purpose of the present invention is to solve the problems of long process preparation time, complex process, low manufacturing efficiency and high manufacturing cost in the existing conductive epoxy resin preparation method, and to provide a preparation method of a high-toughness and high-conductive epoxy resin composition, which has the beneficial effects of excellent product conductivity, short process preparation time, simple process, high manufacturing efficiency and low manufacturing cost.
[0006] The third purpose of the present invention is to solve the problems of poor product conductivity, long process preparation time, complex process, low manufacturing efficiency and high manufacturing cost in the existing conductive epoxy resin and its preparation method, and to provide a use of a high-toughness and high-conductive epoxy resin composition, which has the beneficial effects of excellent product conductivity, short process preparation time, simple process, high manufacturing efficiency and low manufacturing cost.
[0007] In order to achieve one of the purposes of the present invention, the following technical solutions can be adopted:
[0008] A high-toughness and high-conductivity epoxy resin composition, characterized in that it is composed of a base resin, a core-shell resin, a rubber, a curing agent, a wetting agent, an accelerator, a first conductive filler carbon nanotubes, a second conductive filler graphene or conductive graphite, and a third conductive filler spherical conductive carbon black;
[0009] In percentage, the contents of each substance are: 10-20 parts of base resin, 5-10 parts of core-shell resin, 5-10 parts of rubber base material, 0.2-0.4 parts of stearic acid (octadecanoic acid), 2-5 parts of titanate coupling agent (coordination type), 0.1-0.2 parts of vulcanizing agent, 0.2-0.4 parts of curing agent, 0.5-2 parts of wetting agent, 0.01-0.05 parts of accelerator, 1-2 parts of first conductive filler, 20-30 parts of second conductive filler, and 4-8 parts of third conductive filler.
[0010] In order to achieve one of the purposes of the present invention, the following technical solutions can also be adopted:
[0011] Furthermore, the matrix resin may be composed of one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, aliphatic glycidyl ether epoxy resin and glycidyl ester epoxy resin; the core-shell resin may be composed of one or more of core-polybutyl acrylate, shell-PMMA, core-cross-linked polybutadiene, shell-PMMA, core-silicone rubber-shell-PMMA, core-polybutyl acrylate and shell-PMMA.
[0012] Furthermore, the rubber matrix material may be one or more of the pre-vulcanization matrix materials corresponding to carboxyl-terminated nitrile rubber (CTBN), isoprene rubber (IR), nitrile rubber (NBR), and hydrogenated nitrile rubber (HNBR); the titanate coupling agent (coordination type) may be one or more of tetraoctyl titanium [(di(tridecyl phosphite)] (KR-46B) and tetraoctyl titanium [di(dilauryl phosphite)] (KR-46).
[0013] Furthermore, the vulcanizing agent may be one or more of bis-25 vulcanizing agent (2,5-dimethyl-2,5-di(tert-butylperoxy)hexane) and bis-24 vulcanizing agent (2,4-dichloroperoxybenzoyl); the curing agent may be one or more of cyanate curing agent, aliphatic polyamine curing agent, alicyclic polyamine curing agent, aromatic amine curing agent, polyamide curing agent, latent curing agent, Lewis acid-amine complex curing agent, and organic acid anhydride curing agent.
[0014] Furthermore, the wetting agent may be one or more of Efcona 7520, BYK-9076 and BYK-W961; the accelerator may be one or more of imidazole accelerators, peroxide accelerators, azo accelerators, tertiary amine accelerators, phenol accelerators, organic metal salt accelerators and inorganic metal salt accelerators.
[0015] Furthermore, the first conductive filler is: single-walled carbon nanotubes or multi-walled carbon nanotubes with a length of 20-50 μm, preferably carbon nanotubes with a length of 30-40 μm; the second conductive filler is: block graphene or conductive graphite with a particle size of 40-80 μm, preferably block graphene with a particle size of 50-60 μm; further, the third conductive filler is: spherical conductive carbon black with a particle size of 1-10 μm, preferably spherical conductive carbon black with a particle size of 3-5 μm.
[0016] In order to achieve the second purpose of the present invention, the following technical solutions can be adopted:
[0017] A method for preparing a high-toughness and high-conductivity epoxy resin composition, characterized by comprising the following steps:
[0018] 1) Add 10-20 parts of the base resin into a mixer at 60-80°C and preheat for 10 minutes;
[0019] 2) Add 0.2-0.4 parts of stearic acid (octadecanoic acid) and 2-5 parts of titanate coupling agent (coordination type) according to the proportion;
[0020] 3) 4-8 parts of the third conductive filler spherical conductive carbon black and 50% of 1-2 parts of the first conductive filler carbon nanotubes are put into a mixer and melted into the matrix resin for the first banburying at a temperature of 80-120° C., a rotating speed of 30-50 rpm, and a banburying time of 30-60 min;
[0021] 4) After the first banburying is completed, 0.1-0.2 parts of the vulcanizing agent are added to the mixer according to the proportion, and the second banburying is carried out at a banburying temperature of 80-120° C., a rotating speed of the mixer of 20-30 rpm, and a banburying time of 10-30 min to obtain a mixture A;
[0022] 5) mixing 50% of 1-2 parts of carbon nanotubes as the first conductive filler, 20-30 parts of block graphene or conductive graphite, and 0.5-2 parts of a wetting agent, and ultrasonically treating at 40-60° C. for 30-60 min to obtain a composite slurry;
[0023] 6) stirring and mixing the composite slurry obtained in step 5) with butanone to obtain an organic carrier, wherein the amount of butanone added is 50%-100% by weight of the composite slurry, preferably 80%-100%; the stirring and mixing speed is 1500-2000 rpm, and the stirring and mixing time is 2-4 hours;
[0024] 7) grinding the organic carrier obtained in step 5) to an average particle size of 40-60 μm, adding the ground organic carrier to the bisphenol A epoxy resin under stirring, and after the organic carrier is added, adding 5-10 parts of core-shell resin in proportion, stirring and mixing thoroughly, the stirring and mixing speed is 1500-2000 rpm, the stirring and mixing time is 2-4 hours, and then adding 0.2-0.4 parts of curing agent and 0.01-0.05 parts of accelerator in proportion to obtain a mixture B;
[0025] 8) Stirring and mixing the mixture A and the mixture B evenly under heating conditions to obtain a conductive epoxy resin glue; the heating conditions are 60-120° C., and the temperature reaches the liquefaction point of the mixture A, the stirring and mixing speed is 1000-1200 rpm, and the mixing time is 30-60 min.
[0026] In order to achieve the third purpose of the present invention, the following technical solutions can be adopted:
[0027] A use of a high-toughness and high-conductivity epoxy resin composition, characterized in that: a conductive epoxy resin adhesive is prepared by the above method, and a carbon fiber cloth (basic weight 200g / m 2), and then baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 50-55%; then, a prepreg was covered with a release film on both sides, and placed in a programmable temperature and pressure controlled vacuum press, and in a vacuum state, at 25kgf / cm 2 The product was cured at 180°C for 60 minutes to produce a laminate with a thickness of 0.15-0.35 mm.
[0028] The present invention has the following beneficial effects:
[0029] 1. The present invention adds conductive fillers before rubber vulcanization, that is, heats and mixes the rubber before vulcanization, fills more conductive fillers when the viscosity is lower than that at room temperature, selects spherical conductive elastic material with smaller particle size and single-walled carbon nanotubes as filling materials, and uses two conductive fillers of different dimensions to form a double conductive network structure, so that the filling ratio is increased, and the obtained conductive rubber has excellent conductive properties. The vulcanized rubber is prone to agglomeration when passing through a ball mill or a grinder. Therefore, the present invention divides the conductive filler into two parts, one part is mixed with rubber for vulcanization to obtain conductive rubber, and the other part is dispersed by mechanical dispersion, ultrasonic dispersion, ball milling and other dispersion methods and then filled with epoxy resin to obtain conductive epoxy resin, and then the conductive epoxy resin is modified by conductive rubber, and finally a high-toughness and high-conductive epoxy resin is obtained. Therefore, it can solve the problems of poor product conductivity, long process preparation time, complex process, low manufacturing efficiency and high manufacturing cost in the existing conductive epoxy resin and its preparation method, and has the beneficial effects of excellent product conductivity, short process preparation time, simple process, high manufacturing efficiency and low manufacturing cost.
[0030] 2. The present invention forms a double conductive network by compounding conductive fillers, specifically, by compounding two conductive fillers of different dimensions, namely, block fillers and carbon nanotubes. On this basis, well-dispersed spherical conductive fillers with smaller particle sizes are added. The spherical conductive fillers greatly fill the gaps between carbon nanotubes, between block fillers, and between carbon nanotubes and fast fillers; forming a three-dimensional effective conductive network of points, lines, and surfaces, so that the conductive properties of the composition become more excellent. Therefore, the problems of the existing conductive epoxy resin and its preparation method, such as poor product conductive properties, long process preparation time, complex process, low manufacturing efficiency, and high manufacturing cost, can be solved, and the beneficial effects of excellent product conductive properties, short process preparation time, simple process, high manufacturing efficiency, and low manufacturing cost can be achieved.
[0031] 3. The present invention greatly improves the filling ratio of the conductive filler by compounding the first conductive filler, the second conductive filler and the third conductive filler. Adding rubber and core-shell particles to the composition can improve the bonding force of the composition, and at the same time can play a role in toughening and improving impact resistance.
[0032] 4. The high-toughness and high-conductivity epoxy resin composition of the present invention is composed of a base resin, a core-shell resin, a rubber, a curing agent, a wetting agent, an accelerator, a first conductive filler carbon nanotubes, a second conductive filler graphene or conductive graphite, and a third conductive filler spherical conductive carbon black; the content of each substance is: 10-20 parts of base resin, 5-10 parts of core-shell resin, 5-10 parts of rubber base material, 0.2-0.4 parts of stearic acid (octadecanoic acid), 2-5 parts of titanate coupling agent (coordination type), 0.1-0.2 parts of vulcanizing agent, 0.2-0.4 parts of curing agent, 0.5-2 parts of wetting agent, 0.01-0.05 parts of accelerator, 1-2 parts of first conductive filler, 20-30 parts of second conductive filler, and 4-8 parts of third conductive filler. Therefore, it can solve the problems of existing conductive epoxy resins such as poor conductive performance, long process preparation time, complex process, low manufacturing efficiency and high manufacturing cost, and has the beneficial effects of excellent conductive performance, short process preparation time, simple process, high manufacturing efficiency and low manufacturing cost.
[0033] 5. The preparation method of the high-toughness and high-conductivity epoxy resin composition of the present invention comprises the following steps: adding 10-20 parts of the matrix resin to a mixer at 60-80° C. and preheating for 10 minutes; then adding 0.2-0.4 parts of stearic acid (octadecanoic acid) and 2-5 parts of a titanate coupling agent (coordination type) in proportion; and then adding 4-8 parts of a third conductive filler, 50% of 1-2 parts of a first conductive filler, carbon nanotubes, into the mixer and the melted matrix resin in proportion. The first banburying temperature is 80-120°C, the speed of the mixer is 30-50rpm, and the banburying time is 30-60min; after the first banburying is completed, 0.1-0.2 parts of the vulcanizing agent are added to the mixer according to proportion, and the second banburying is carried out at a banburying temperature of 80-120°C, the speed of the mixer is 20-30rpm, and the banburying time is 10-30min; a mixture A is obtained; 50% of 1-2 parts of the first conductive filler carbon nanotubes, block graphene or conductive graphite 20-30 parts of cellulose and 0.5-2 parts of wetting agent are mixed, and ultrasonic treatment is performed at 40-60°C for 30-60 minutes to obtain a composite slurry; the obtained composite slurry is stirred and mixed with butanone to obtain an organic carrier, and the butanone addition amount is 50%-100% by weight of the composite slurry, preferably 80%-100%; the stirring and mixing speed is 1500-2000rpm, and the stirring and mixing time is 2-4h; the obtained organic carrier is ground to an average particle size of 40-60μm, and In the state, the ground organic carrier is added to the bisphenol A epoxy resin. After the organic carrier is added, 5-10 parts of core-shell resin are added in proportion, and the mixture is fully stirred and mixed. The stirring and mixing speed is 1500-2000rpm, and the stirring and mixing time is 2-4h. Then, 0.2-0.4 parts of curing agent and 0.01-0.05 parts of accelerator are added in proportion to obtain mixture B; the mixture A and mixture B are stirred and mixed evenly under heating conditions to obtain conductive epoxy resin glue. Therefore, the problems of long process preparation time, complex process, low manufacturing efficiency and high manufacturing cost in the existing conductive epoxy resin preparation method can be solved, and the product has the beneficial effects of excellent conductive performance, short process preparation time, simple process, high manufacturing efficiency and low manufacturing cost. DETAILED DESCRIPTION Specific embodiment 1:
[0035] The high-toughness and high-conductivity epoxy resin composition involved in this specific embodiment 1 is characterized by being composed of a base resin, a core-shell resin, a rubber, a curing agent, a wetting agent, a accelerator, a first conductive filler carbon nanotubes, a second conductive filler in the form of graphene or conductive graphite, and a third conductive filler spherical conductive carbon black; in terms of percentage, the content of each substance is: 10-20 parts of base resin, 5-10 parts of core-shell resin, 5-10 parts of rubber base material, 0.2-0.4 parts of stearic acid (octadecanoic acid), 2-5 parts of titanate coupling agent (coordination type), 0.1-0.2 parts of vulcanizing agent, 0.2-0.4 parts of curing agent, 0.5-2 parts of wetting agent, 0.01-0.05 parts of accelerator, 1-2 parts of first conductive filler, 20-30 parts of second conductive filler, and 4-8 parts of third conductive filler.
[0036] In this embodiment:
[0037] The matrix resin can be composed of one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, aliphatic glycidyl ether epoxy resin and glycidyl ester epoxy resin; the core-shell resin can be composed of one or more of core-polybutyl acrylate, shell-PMMA, core-cross-linked polybutadiene, shell-PMMA, core-silicone rubber-shell-PMMA, core-polybutyl acrylate, shell-PMMA.
[0038] The rubber matrix material can be: one or more of the pre-vulcanization matrix materials corresponding to carboxyl-terminated nitrile rubber (CTBN), isoprene rubber (IR), nitrile rubber (NBR), and hydrogenated nitrile rubber (HNBR); the titanate coupling agent (coordination type) can be: one or more of tetraoctyl titanium [(di(tridecyl phosphite)] (KR-46B) and tetraoctyl titanium [di(dilauryl phosphite)] (KR-46).
[0039] The vulcanizing agent can be one or more of bis-25 vulcanizing agent (2,5-dimethyl-2,5-di(tert-butylperoxy)hexane) and bis-24 vulcanizing agent (2,4-dichloroperoxybenzoyl); the curing agent can be one or more of cyanate curing agent, fatty polyamine curing agent, alicyclic polyamine curing agent, aromatic amine curing agent, polyamide curing agent, latent curing agent, Lewis acid-amine complex curing agent, and organic acid anhydride curing agent.
[0040] The wetting agent can be one or more of Efcona 7520, BYK-9076 and BYK-W961; the accelerator can be one or more of imidazole accelerators, peroxide accelerators, azo accelerators, tertiary amine accelerators, phenol accelerators, organic metal salt accelerators and inorganic metal salt accelerators.
[0041] The first conductive filler is: single-walled carbon nanotubes or multi-walled carbon nanotubes with a length of 20-50 μm, preferably carbon nanotubes with a length of 30-40 μm; the second conductive filler is: block graphene or conductive graphite with a particle size of 40-80 μm, preferably block graphene with a particle size of 50-60 μm; further, the third conductive filler is: spherical conductive carbon black with a particle size of 1-10 μm, preferably spherical conductive carbon black with a particle size of 3-5 μm.
[0042] The preparation method involved in this specific embodiment 1 is characterized by comprising the following steps:
[0043] 1) Add 10-20 parts of the base resin into a mixer at 60-80°C and preheat for 10 minutes;
[0044] 2) Add 0.2-0.4 parts of stearic acid (octadecanoic acid) and 2-5 parts of titanate coupling agent (coordination type) according to the proportion;
[0045] 3) 4-8 parts of the third conductive filler spherical conductive carbon black and 50% of 1-2 parts of the first conductive filler carbon nanotubes are put into a mixer and melted into the matrix resin for the first banburying at a temperature of 80-120° C., a rotating speed of 30-50 rpm, and a banburying time of 30-60 min;
[0046] 4) After the first banburying is completed, 0.1-0.2 parts of the vulcanizing agent are added to the mixer according to the proportion, and the second banburying is carried out at a banburying temperature of 80-120° C., a rotating speed of the mixer of 20-30 rpm, and a banburying time of 10-30 min to obtain a mixture A;
[0047] 5) mixing 50% of 1-2 parts of carbon nanotubes as the first conductive filler, 20-30 parts of block graphene or conductive graphite, and 0.5-2 parts of a wetting agent, and ultrasonically treating at 40-60° C. for 30-60 min to obtain a composite slurry;
[0048] 6) stirring and mixing the composite slurry obtained in step 5) with butanone to obtain an organic carrier, wherein the amount of butanone added is 50%-100% by weight of the composite slurry, preferably 80%-100%; the stirring and mixing speed is 1500-2000 rpm, and the stirring and mixing time is 2-4 hours;
[0049] 7) grinding the organic carrier obtained in step 5) to an average particle size of 40-60 μm, adding the ground organic carrier to the bisphenol A epoxy resin under stirring, and after the organic carrier is added, adding 5-10 parts of core-shell resin in proportion, stirring and mixing thoroughly, the stirring and mixing speed is 1500-2000 rpm, the stirring and mixing time is 2-4 hours, and then adding 0.2-0.4 parts of curing agent and 0.01-0.05 parts of accelerator in proportion to obtain a mixture B;
[0050] 8) Stirring and mixing the mixture A and the mixture B evenly under heating conditions to obtain a conductive epoxy resin glue; the heating conditions are 60-120° C., and the temperature reaches the liquefaction point of the mixture A, the stirring and mixing speed is 1000-1200 rpm, and the mixing time is 30-60 min.
[0051] The use involved in this embodiment is characterized by:
[0052] The CTBN matrix material of the weight part is added to a mixer at 60-80° C. and preheated for 10 minutes, and the stearic acid and the coupling agent KR-46 are added, and the spherical conductive carbon black and the single-walled carbon nanotubes of 50% of the weight part are added to the melted CTBN matrix material in batches, and the first banburying is performed, and the banburying temperature is preferably 80-120° C., the rotation speed is 30-50 rpm, and the time is 30-60 minutes. After the first banburying is completed, the bis-25 vulcanizing agent of the weight part is added to the mixer, and the second banburying is performed, and the banburying temperature is preferably 80-120° C., the rotation speed is 20-30 rpm, and the time is 10-30 minutes; obtain a mixture A;
[0053] 50% of the weight portion of single-walled carbon nanotubes, the weight portion of block graphene, and Evcona 7520 are mixed, and ultrasonic treatment is performed at 40-60°C for 30-60 minutes to obtain a composite slurry; the composite slurry is stirred and mixed with butanone to obtain an organic carrier, and the butanone addition amount is 50%-100% of the weight of the composite slurry, preferably 80%-100%. The stirring and mixing speed is 1500-2000rpm, and the stirring and mixing time is 2-4h; the organic carrier is ground to an average particle size of 40-60μm, and the ground organic carrier is added to the bisphenol A epoxy resin under stirring. After the organic carrier is added, the weight portion of core-shell resin is added and fully stirred and mixed. The stirring and mixing speed is 1500-2000rpm, and the stirring and mixing time is 2-4h. Finally, the weight portions of dicyandiamide and 2-methylimidazole are added to finally obtain a mixture B;
[0054] Mixture A and mixture B are stirred and mixed evenly under heating conditions to obtain a conductive epoxy resin glue solution. The heating conditions are 60-120°C, and the temperature reaches the liquefaction point of mixture A. The stirring and mixing speed is 1000-1200rpm, and the mixing time is 30-60min;
[0055] Use this glue to impregnate carbon fiber cloth (basic weight 200g / m 2 ), and then baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 50-55%. Cover the upper and lower sides of a prepreg with a release film, place it in a vacuum press with programmable temperature and pressure control, and press it under vacuum at 25kgf / cm 2 The product was cured at 180°C for 60 minutes to produce a laminate with a thickness of 0.25 mm. Specific embodiment 2:
[0057] The characteristic of this specific embodiment 2 is that the proportion of bisphenol A epoxy resin in embodiment 1 is increased from 10 parts to 15 parts. The preparation method and use are the same as those in specific embodiment 1. Specific embodiment 3:
[0059] The characteristic of this specific embodiment 3 is that the percentage of bisphenol A epoxy resin in specific embodiment 1 is increased from 10 parts to 20 parts. The preparation method and use are the same as those in specific embodiment 1. Specific embodiment 4:
[0061] The characteristic of this specific embodiment 4 is that the core-shell resin content in specific embodiment 1 is increased from 5 parts to 10 parts. The preparation method and use are the same as those in specific embodiment 1. Specific embodiment 5:
[0063] The characteristic of this specific embodiment 5 is that the proportion of the CTBN matrix material in the embodiment 1 is increased from 5 parts to 10 parts. The preparation method and use are the same as those of the specific embodiment 1. Specific embodiment 6:
[0065] The characteristics of this specific embodiment 6 are: the proportion of bisphenol A epoxy resin in specific embodiment 1 is increased from 10 parts to 20 parts by percentage; the proportion of core-shell resin in specific embodiment 1 is increased from 5 parts to 10 parts by percentage; the proportion of CTBN matrix material in embodiment 1 is increased from 5 parts to 10 parts by percentage. The preparation method and use are the same as those in specific embodiment 1. Specific embodiment 7:
[0067] The characteristic of this specific embodiment 7 is that the percentage of block graphene in embodiment 1 is increased from 20 to 25. The preparation method and use are the same as those in specific embodiment 1. Specific embodiment 8:
[0069] The characteristic of this specific embodiment 8 is that the percentage of block graphene in embodiment 1 is increased from 20 to 30. The preparation method and use are the same as those of specific embodiment 1. Specific embodiment 9:
[0071] The characteristics of this specific embodiment 9 are: the percentage of single-walled carbon nanotubes in embodiment 1 is increased from 1 to 2, and the percentage of block graphene in embodiment 1 is increased from 20 to 25. The preparation method and use are the same as those in specific embodiment 1. Specific embodiment 10:
[0073] The characteristics of this specific embodiment 10 are: the percentage of single-walled carbon nanotubes in embodiment 1 is increased from 1 to 2, and the percentage of block graphene in embodiment 1 is increased from 20 to 30. The preparation method and use are the same as those of specific embodiment 1.
[0074] Comparative Example 1:
[0075] The preparation method is the same as that of Example 1, except that the weight of the bisphenol A epoxy resin in Example 1 is increased from 10 to 15, and the core-shell resin is not added.
[0076] Comparative Example 2:
[0077] The weight portion of single-walled carbon nanotubes, the weight portion of block graphene, the weight portion of spherical conductive carbon black, and Evcona 7520 are mixed, and ultrasonic treatment is performed at 40-60°C for 30-60min to obtain a composite slurry; the composite slurry is stirred and mixed with butanone to obtain an organic carrier, and the butanone addition amount is 50%-100% of the weight of the composite slurry, preferably 80%-100%. The stirring and mixing speed is 1500-2000rpm, and the stirring and mixing time is 2-4h; the organic carrier is ground to an average particle size of 40-60μm, and the ground organic carrier is added to the bisphenol A epoxy resin under stirring. After the organic carrier is added, the weight portion of core-shell resin is added, and the stirring and mixing is fully performed. The stirring and mixing speed is 1500-2000rpm, and the stirring and mixing time is 2-4h. Finally, the weight portion of dicyandiamide and 2-methylimidazole are added to obtain a conductive epoxy resin glue.
[0078] Use this glue to impregnate carbon fiber cloth (basic weight 200g / m 2), and then baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 50-55%. Cover the upper and lower sides of a prepreg with a release film, place it in a vacuum press with programmable temperature and pressure control, and press it under vacuum at 25kgf / cm 2 The product was cured at 180°C for 60 minutes to produce a laminate with a thickness of 0.25 mm.
[0079] Comparative Example 3:
[0080] The preparation method is the same as that of Example 1, except that the weight of the single-walled carbon nanotubes in Example 1 is increased from 1 to 25, and blocky graphene and spherical conductive carbon black are not added.
[0081] Comparative Example 4:
[0082] The preparation method is the same as in Example 1, except that Efcona 7520 is not added.
[0083] Comparative Example 5:
[0084] The preparation method is the same as that of Example 1, except that the weight of the single-walled carbon nanotubes in Example 1 is increased from 1 to 2, the weight of the block graphene is increased from 20 to 30, and no spherical conductive carbon black is added.
[0085] Comparative Example 6:
[0086] The preparation method is the same as that of Example 1, except that the weight of the single-walled carbon nanotubes in Example 1 is increased from 1 to 2, the weight of the spherical conductive carbon black is increased from 4 to 30, and no blocky graphene is added.
[0087] Volume resistivity test method: GB / T 15662-1995
[0088] Impact strength test method: GB / T 1843-2008
[0089] Elongation at break test method: GB / T 2567-2008
[0090]
[0091]
[0092]
[0093]
[0094] According to the test results, Examples 1-10 and Comparative Examples 1-6 were evaluated:
[0095] The conductive epoxy resin and the composition thereof of the present invention have excellent conductive properties and maintain toughness and impact resistance without degradation.
[0096] According to the test results, Example 1 and Comparative Examples 3 and 4 were evaluated:
[0097] The addition of wetting agent and the reasonable compounding of single-walled carbon nanotubes, blocky graphene and spherical conductive carbon black can effectively achieve high filling of conductive filler without defects on the surface of the sheet.
[0098] According to the test results, Example 1 and Comparative Examples 5 and 6 were evaluated:
[0099] The reasonable combination of single-walled carbon nanotubes, blocky carbon nanotubes and spherical conductive carbon black forms more conductive networks than the combination of any two of them, and the reasonable combination has better conductive properties than the composite obtained by simply increasing the filling ratio.
[0100] The problem that the toughness of the composition deteriorates and the bonding force decreases when the conductive filler is highly filled is solved. Compared with the conductive silver powder filled in the same proportion, the volume resistivity of the composition is similar, but the composition of the present invention is lighter. The filling ratio of the conductive filler is greatly improved by compounding the first conductive filler, the second conductive filler and the third conductive filler. Adding rubber and core-shell particles to the composition can improve the bonding force of the composition, and at the same time can play the role of toughening and improving impact resistance.
[0101] The present invention adopts core-shell resin toughening, and the rubber body of the core layer toughens the epoxy resin, and the shell layer protects the core body to keep its original shape, and utilizes physical or chemical effects with the epoxy resin matrix to improve the dispersibility and compatibility of the core body in the matrix, while improving the toughness of the epoxy resin without reducing the glass transition temperature. The toughening of the core-shell resin solves the brittleness problem caused by high filling of the conductive filler, and the comprehensive performance of the composition does not decrease.
[0102] The present invention forms a large number of silver streaks and shear bands in the composite system by toughening the rubber and improving the bonding strength. When subjected to stress, the silver streaks will turn and branch when they meet each other or when they meet rubber particles, which can increase energy absorption and improve the toughness of the material. The three-dimensional network structure formed by the rubber and epoxy resin during the curing process is like countless small anchors, firmly bonding the conductive filler, the reinforcing substrate, and the epoxy resin matrix together, thereby improving the bonding strength.
[0103] The present invention adds conductive fillers before rubber vulcanization, and the viscosity of the rubber before vulcanization (compared with after vulcanization) is low. When heated and mixed, the viscosity is lower than that at room temperature, and more conductive fillers can be filled. Spherical conductive elastics with smaller particle sizes and single-walled carbon nanotubes are selected as filling materials. Two conductive fillers of different dimensions are used in combination to provide a double conductive network structure, and the filling ratio is higher, so that the obtained conductive rubber has excellent conductive properties. The vulcanized rubber is prone to agglomeration when passing through a ball mill or a grinder. Therefore, the present invention divides the conductive filler into two parts, one part is mixed with rubber for vulcanization to obtain conductive rubber, and the other part is dispersed by mechanical dispersion, ultrasonic dispersion, ball milling and other dispersion methods and then filled with epoxy resin to obtain conductive epoxy resin, and then the conductive epoxy resin is modified by the conductive rubber to finally obtain high-toughness and high-conductivity epoxy resin.
[0104] The present invention adopts stearic acid, which improves the dispersion effect of the conductive filler, facilitates the full dispersion of the conductive filler, and reduces the tendency of the mixed rubber to stick to the roller. Stearic acid plays an important role in the synthesis and processing of rubber. Stearic acid is a vulcanization activator widely used in natural rubber, synthetic rubber and latex, and can also be used as a plasticizer and softener. Stearic acid needs to be added as an emulsifier in the production process of synthetic rubber. When making foam rubber, stearic acid can be used as a foaming agent. Stearic acid can also be used as a release agent for rubber products.
[0105] The present invention adopts a titanate coupling agent (coordination type), which has a good coupling effect when used in a variety of resin-based or rubber-based composite material systems, and overcomes the disadvantages of using a general titanate coupling agent in a resin-based composite material system. In addition, the filling amount of the inorganic filler can be increased, the amount of rubber used can be reduced, and the production cost can be reduced. The compatibility of the inorganic filler and the rubber is improved, the filler can be more dispersed in the resin, the melt viscosity is reduced, the processing performance is improved, and the efficiency is improved; the mechanical properties of the product such as the impact strength, tensile strength, and flexibility are improved.
[0106] The present invention adopts a conductive filler compound, and forms a double conductive network by compounding two conductive fillers of different dimensions, namely, block fillers and carbon nanotubes. On this basis, well-dispersed spherical conductive fillers with smaller particle sizes are added. The spherical conductive fillers greatly fill the gaps between carbon nanotubes, between block fillers, and between carbon nanotubes and fast fillers; thus, a three-dimensional effective conductive network of points, lines, and surfaces is formed, so that the conductive performance of the composition becomes even better.
[0107] In summary, the present invention has strong bonding strength and excellent conductive properties, and is widely applicable to the fields of electronics, electrical appliances, automobiles, aviation, medical instruments, etc.
Claims
1. A high-toughness and high-conductivity epoxy resin composition, characterized in that: It consists of a base resin, a core-shell resin, a rubber, a curing agent, a wetting agent, an accelerator, a first conductive filler carbon nanotube, a second conductive filler graphene or conductive graphite, and a third conductive filler spherical conductive carbon black; In percentage, the contents of each substance are: 10-20 parts of base resin, 5-10 parts of core-shell resin, 5-10 parts of rubber base material, 0.2-0.4 parts of stearic acid (octadecanoic acid), 2-5 parts of titanate coupling agent (coordination type), 0.1-0.2 parts of vulcanizing agent, 0.2-0.4 parts of curing agent, 0.5-2 parts of wetting agent, 0.01-0.05 parts of accelerator, 1-2 parts of first conductive filler, 20-30 parts of second conductive filler, and 4-8 parts of third conductive filler.
2. The high-toughness and high-conductivity epoxy resin composition according to claim 1, characterized in that: The matrix resin is composed of one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, aliphatic glycidyl ether epoxy resin and glycidyl ester epoxy resin; the core-shell resin can be composed of one or more of core-polybutyl acrylate, shell-PMMA, core-cross-linked polybutadiene, shell-PMMA, core-silicone rubber-shell-PMMA, core-polybutyl acrylate and shell-PMMA.
3. The high-toughness and high-conductivity epoxy resin composition according to claim 1, characterized in that: The rubber matrix material is composed of one or more of the pre-vulcanization matrix materials corresponding to carboxyl-terminated nitrile rubber (CTBN), isoprene rubber (IR), nitrile rubber (NBR), and hydrogenated nitrile rubber (HNBR); the titanate coupling agent (coordination type) can be composed of one or more of tetraoctyl titanium [(di(tridecyl phosphite)] (KR-46B) and tetraoctyl titanium [di(dilauryl phosphite)] (KR-46).
4. The high-toughness and high-conductivity epoxy resin composition according to claim 1, characterized in that: The vulcanizing agent is one or more of bis-25 vulcanizing agent (2,5-dimethyl-2,5-di(tert-butylperoxy)hexane) and bis-24 vulcanizing agent (2,4-dichloroperoxybenzoyl); the curing agent can be one or more of cyanate curing agent, fatty polyamine curing agent, alicyclic polyamine curing agent, aromatic amine curing agent, polyamide curing agent, latent curing agent, Lewis acid-amine complex curing agent, and organic acid anhydride curing agent.
5. The high-toughness and high-conductivity epoxy resin composition according to claim 1, characterized in that: The wetting agent is one or more of Efcona 7520, BYK-9076 and BYK-W961; the accelerator can be one or more of imidazole accelerators, peroxide accelerators, azo accelerators, tertiary amine accelerators, phenol accelerators, organic metal salt accelerators and inorganic metal salt accelerators.
6. The high-toughness and high-conductivity epoxy resin composition according to claim 1, characterized in that: The first conductive filler is: single-walled carbon nanotubes or multi-walled carbon nanotubes with a length of 20-50 μm, preferably carbon nanotubes with a length of 30-40 μm; the second conductive filler is: block graphene or conductive graphite with a particle size of 40-80 μm, preferably block graphene with a particle size of 50-60 μm; further, the third conductive filler is: spherical conductive carbon black with a particle size of 1-10 μm, preferably spherical conductive carbon black with a particle size of 3-5 μm.
7. A method for preparing a high-toughness and high-conductivity epoxy resin composition, characterized in that The steps include: 1) Add 10-20 parts of the base resin into a mixer at 60-80°C and preheat for 10 minutes; 2) Add 0.2-0.4 parts of stearic acid (octadecanoic acid) and 2-5 parts of titanate coupling agent (coordination type) according to the proportion; 3) 4-8 parts of the third conductive filler spherical conductive carbon black and 50% of 1-2 parts of the first conductive filler carbon nanotubes are put into a mixer and melted into the matrix resin for the first banburying at a temperature of 80-120° C., a rotating speed of 30-50 rpm, and a banburying time of 30-60 min; 4) After the first banburying is completed, 0.1-0.2 parts of the vulcanizing agent are added to the mixer according to the proportion, and the second banburying is carried out at a banburying temperature of 80-120° C., a rotating speed of the mixer of 20-30 rpm, and a banburying time of 10-30 min to obtain a mixture A; 5) mixing 50% of 1-2 parts of carbon nanotubes as the first conductive filler, 20-30 parts of block graphene or conductive graphite, and 0.5-2 parts of a wetting agent, and ultrasonically treating at 40-60° C. for 30-60 min to obtain a composite slurry; 6) stirring and mixing the composite slurry obtained in step 5) with butanone to obtain an organic carrier, wherein the amount of butanone added is 50%-100% by weight of the composite slurry, preferably 80%-100%; the stirring and mixing speed is 1500-2000 rpm, and the stirring and mixing time is 2-4 hours; 7) grinding the organic carrier obtained in step 5) to an average particle size of 40-60 μm, adding the ground organic carrier to the bisphenol A epoxy resin under stirring, and after the organic carrier is added, adding 5-10 parts of core-shell resin in proportion, stirring and mixing thoroughly, the stirring and mixing speed is 1500-2000 rpm, the stirring and mixing time is 2-4 hours, and then adding 0.2-0.4 parts of curing agent and 0.01-0.05 parts of accelerator in proportion to obtain a mixture B; 8) Stirring and mixing the mixture A and the mixture B evenly under heating conditions to obtain a conductive epoxy resin glue; the heating conditions are 60-120° C., and the temperature reaches the liquefaction point of the mixture A, the stirring and mixing speed is 1000-1200 rpm, and the mixing time is 30-60 min.
8. Use of a high-toughness and high-conductivity epoxy resin composition, characterized in that: The conductive epoxy resin glue was prepared by the above method, and the carbon fiber cloth (basic weight 200g / m 2 ), and then baked in a hot air circulation oven at 170°C for 2 minutes to obtain a prepreg with a resin content of 50-55%; then, a prepreg was covered with a release film on both sides, and placed in a programmable temperature and pressure controlled vacuum press, and in a vacuum state, at 25kgf / cm 2 The product was cured at 180°C for 60 minutes to produce a laminate with a thickness of 0.15-0.35 mm.
Citation Information
Patent Citations
A highly conductive epoxy resin adhesive and its preparation method
CN108165198B
A toughened conductive epoxy resin composite material and its preparation method
CN110256815B
Cited By
Low-change-rate slurry as well as preparation and application thereof
CN119786121A
